2014
DOI: 10.1007/s10750-014-1882-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem impacts of the invasive bivalve Limnoperna fortunei (golden mussel) in South America

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer International Publishing Switzerland. This eoffprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 75 publications
(143 reference statements)
2
58
0
9
Order By: Relevance
“…However, if the quantity of this subsidy was low (30 g / 0.25 m 2 ), the effects can be positive with a higher invertebrate richness [140]. Some invasive species may be beneficial to native species, but they can interrupt important energetic subsidy flows into other ecosystems which may cause ecosystem-scale consequences [141].…”
Section: Impacts Of Landscape Disturbance On Cross-ecosystem Subsidiementioning
confidence: 99%
“…However, if the quantity of this subsidy was low (30 g / 0.25 m 2 ), the effects can be positive with a higher invertebrate richness [140]. Some invasive species may be beneficial to native species, but they can interrupt important energetic subsidy flows into other ecosystems which may cause ecosystem-scale consequences [141].…”
Section: Impacts Of Landscape Disturbance On Cross-ecosystem Subsidiementioning
confidence: 99%
“…In North America, for example, Zebra mussels (Dreissena polymorpha), which were transported from Europe to North America in the ballast water of ships in the mid-eighties, have been shown to negatively impact aquatic ecosystems by harming native organisms by outcompeting other filter feeders or by adhering to shells of native mussels, turtles, and crustaceans [55]. Another example of invasion is the introduction in the Parana basin of an even more dangerous species, Limnoperna fortunei, which has a glochidia larvae that can attach to fishes to be transported upstream [56]. According to The Global Invasive Species Database (GISD), however, the most aggressive alien mussel species is probably M. galloprovincialis, a native from the Mediterranean coast and the Black and Adriatic Seas.…”
Section: Impacts Of Climate Change and Pollution On Mixed Mussel Bedsmentioning
confidence: 99%
“…Numerous reports have shown that the same introduced species can have very dissimilar effects in different habitats, and even within the same habitat, with changing environmental conditions (Byers et al 2002 (Boltovskoy and Correa 2015). This approach hampers objective analyses and does little to advance our understanding of how this species interacts with its new environment.…”
Section: Japanmentioning
confidence: 99%